1983
DOI: 10.1136/bjsm.17.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Effects of menstruation and contraceptive pill on the performance of physical education students.

Abstract: Of the 109 specialist female physical education students who answered a detailed questionnaire on menstruation and the contraceptive pill in relation to exercise, 91 (83.5%) reported that they suffered menstrual problems. These included stomach ache, depression, abdominal cramps and backache. Over two-thirds of the students considered that these problems adversely influenced their physical performance. However, whether they had a mainly physiological or psychological effect is not clear. Many of the students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…However, it was significantly lower in LP compared with FP only for the 2 final sprints (p , 0.05, h 2 p 5 0.44). This result is in agreement with previous studies demonstrating a higher performance in swimming sprints and multiple cycling sprints during FP (2,27). Conversely, some other studies reported better total work after 10 times 6 repeated sprint cycling ( 24) and a better performance in specific judo tasks (38) during the LP compared with mid-FP.…”
Section: Discussionsupporting
confidence: 94%
“…However, it was significantly lower in LP compared with FP only for the 2 final sprints (p , 0.05, h 2 p 5 0.44). This result is in agreement with previous studies demonstrating a higher performance in swimming sprints and multiple cycling sprints during FP (2,27). Conversely, some other studies reported better total work after 10 times 6 repeated sprint cycling ( 24) and a better performance in specific judo tasks (38) during the LP compared with mid-FP.…”
Section: Discussionsupporting
confidence: 94%
“…However, combination OCAs were associated with reduced handgrip endurance time and force output (39). Aerobic performance declined in some OCA users (9,22,28) and did not in others (1,6,10,19,22), and OCA use does not appear to affect anaerobic performance (10,22,24).…”
Section: Introductionmentioning
confidence: 91%
“…When considering RED‐S, prevention is better than cure, owing to the potentially irreversible nature of the long‐term health associations. Given that more than two‐thirds of sportswomen report adverse effects from menstruation on their performance, amenorrhoea associated with RED‐S may be welcome to uninformed sportswomen. Therefore, it is essential that all sportswomen and associated personnel must be made fully aware of the aetiology and short‐term and long‐term performance and health‐related risks of RED‐S.…”
Section: Managementmentioning
confidence: 99%